Pisownia afrykat „c” i „č” w Ewangeliarzu Tip-7 ze zbioru Rosyjskiego Państwowego Archiwum Akt Dawnych f. 381, nr 7 - Szwed, Zofia (Studia Rossica Posnaniensia, 2018)
The paper touches upon the phenomenon of interchanging consonants c and č in the text of the full lectionary from the Russian State Archive of Ancient Acts in Moscow. The research aims at establishing orthographical rules which were followed by the writers of the book, as well as at defining the number and categories of mistakes which were made by the writers while breaking the aforementioned rules. The research findings amount to a linguistic confirmation of the northern origins of the Gospel Book Tip-7. Moreover, the results are the basis for assessing the level of the writers’ professionalism and for comparing this old text with other manuscripts created in similar locations and times.